Smoking-Induced Inhibition of Number and Activity of Endothelial Progenitor Cells and Nitric Oxide in Males Were Reversed by Estradiol in Premenopausal Females - Yijia Shao; Liang Luo; Zi Ren; Jiayi Guo; Xingxing Xiao; Jiana Huang; Haitao Zeng; Hong Zhan (Cardiology Research and Practice)
Objectives. The number and activity of circulating EPCs were enhanced in premenopausal women contrast to postmenopausal females and age-matched males. Here, we investigated whether this favorable effect exists in premenopausal women and age-matched men with cigarette smoking. Methods. In a cross-sectional study, the number and activity of circulating EPCs and nitric oxide production (NO) as well as flow-mediated vasodilation (FMD) in both premenopausal women and age-matched men with or without cigarette smoking were studied. Results. Compared with age-matched men with or without smoking, the number and function of circulating EPCs as well as NO level in premenopausal women were obviously higher than that in the former and not affected by smoking. The number and function of circulating EPCs as well as NO level in male smokers were shown to be the most strongly inhibited. Furthermore, there was significant correlation between EPC number and activity, plasma NO level, and NO secretion by EPCs and FMD. Conclusions. Estradiol was deemed to play an important role in enhancing the number and activity of EPCs and NO production in premenopausal women even when affected by smoking, which may be the important mechanisms underlying vascular protection of estradiol in premenopausal women, but not in age-matched men.